Moderate alcohol intake and heart rate variability adaptations to high-intensity interval training in healthy young adults: the BEER-HIIT study - Ginés Navarro-Lomas; Alejandro De-la-O; Manuel Dote-Montero; Manuel J. Castillo; Francisco J. Amaro-Gahete; Abel Plaza-Florido (Frontiers in Cardiovascular Medicine, 2026)
Background It is unknown whether daily alcohol consumption influences training effects on heart rate variability (HRV). This study investigated: (i) the effects of a 10-week high-intensity interval training (HIIT) on HRV in healthy young adults; and (ii) the effects of daily alcohol consumption on HRV responses to exercise. Methods 71 healthy young adults (18–40 years old; 52.1% women) participated in the BEER-HIIT study. We conducted a 10-week (2 days/week) controlled trial (ClinicalTrials.gov ID: NCT03660579). Participants were allocated to 5 groups: a non-training group (N-T) and four HIIT groups. Participants in the training groups chose whether to consume alcohol. Those choosing alcohol were randomly allocated to receive beer (5.4%; T-Beer) or an equivalent amount of alcohol (vodka; T-Ethanol) in sparkling water. Those choosing no alcohol were randomly allocated to receive alcohol-free beer (0.0%; T-Zero) or sparkling water (T-Water). Training comprised eight weight-bearing exercises performed in circuit form. HRV was measured before and after the intervention. Results No statistically significant between-group differences in HRV outcomes were detected after the intervention (all p > 0.05). Conclusions Our findings indicate that: (i) no statistically significant differences in HRV responses were detected following a 10-week HIIT program using weight-bearing exercises performed twice per week; and (ii) no statistically significant differences in HRV responses were observed among the assigned beverage intervention groups. These findings should be interpreted cautiously because HRV was a secondary outcome and the study was not specifically powered to detect differences in these parameters.